Women entrepreneurial career maturity towards success of business in Semarang, Indonesia - Darmanto, Susetyo; Ponmalar N Alagappar,; Jesrina Ann Xavier, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper investigates the influence of career maturity amongst women entrepreneurs in Semarang, Indonesia towards the success of their business. Based on theoretical perspectives and empirical contribution, an integrated research model was developed focusing on entrepreneurial orientation, entrepreneurial experience, need for achievement and instrumental readiness. The respondents were 110 women entrepreneurs from Semarang, Indonesia. Results demonstrated that the entrepreneurial orientation, need for achievement and entrepreneurial experience positively influenced woman entrepreneurial career maturity. Entrepreneurial orientation and need for achievement showed a positive influence on success of business. The women entrepreneurial career maturity had a significant and positive effect on success of business. However, the effects of instrumental readiness on women entrepreneurial career maturity and success of business were insignificant, and the effect of entrepreneur experience on success of business was also insignificant. This paper is imperative in offering practical insights into the strategic role of women entrepreneurs, which may be a significant a factor in their entrepreneurial success.